AVALIACAO DE BERGAPTENO 3CH E 6CH NA PROTECAO DE PEPINEIROS (CUCUMIS SATIVUS) CONTRA INTOXICACOES POR ESSA MESMA SUBSTANCIA - Peach, L. T. [UNESP]; Pozetti, G. L. [UNESP]; Lepera, José Salvador [UNESP] (My University, 1994)
Authors report trial with bergapten using homeopathic preparations and the protection of cucumber seedlings (Cucumis sativus) against intoxications by the same substance and assess the positive results obtained.
Bergapten's assess to protect cucumber seedlings (Cucumis sativus) against intoxications by the same substance
Keywords: bergapten; homeopathy; homeopathic agent; intoxication